The impact of fuelling and W radiation on the performance of high-power, ITER-baseline scenario plasmas in JET-ILW. (11th August 2021) - Field, A R; Aleiferis, S; Belonohy, É; Carvalho, P; Coffey, I; Frigione, D; Garzotti, L; Horvath, L; Kim, Hyun-Tae; Lennholm, M; Lerche, E; Lomas, P; et al.
Abstract: Sustained operation of high-performance, ITER-baseline scenario plasmas at the high levels of input power ( ≲ 40 MW ) required to achieve ∼15 MW of D-T fusion power in JET-ILW requires careful optimisation of the fuelling to avoid an unacceptable disruption rate due to excessive radiation, primarily from W impurities, which are sputtered by edge-localised modes (ELMs) from the divertor targets. By using a train of ELM-pacing pellets from a high-frequency pellet injector to promote regular ELMs, which flush W and other impurities from the confined plasma, such high-performance plasmas can be sustained (for ∼5 s) while maintaining a high normalised confinement factor H 98, y 2 ∼ 1, which would otherwise be degraded by reducing the pedestal confinement if a higher rate of D2 gas fuelling were used instead of the pellets to mitigate the W contamination. The causes underlying the improved performance and energy confinement obtained using this combined, gas and pellet fuelling scheme is investigated here in some detail.